REORIENTASI PENDIDIKAN MORAL ISLAM DALAM PEMBINAAN KARAKTER SISWA: Reorientation of islamic moral educationIn character building of students - Mutamakin, Mutamakin (STAI Ma'had Aly Al-Hikam Malang, 2024)
ABSTRACT Education plays an important role in the development of Islamic morals (akhlak). In Islam, Islamic moral teachings play an important role in guiding individuals to live a pious life. Morals in Islam are essentially the basic values ​​and foundations of a person's character. This study attempts to describe and analyze Islamic moral education. This study uses a library method that uses text sources such as journals and books. The results of this study indicate that Islamic moral development faces the influence and challenges of global secularism and a lack of resources. The solution to facing these challenges is primarily through a training program for Educators. Furthermore, Islamic moral education can be implemented in the school curriculum through the integration of the curriculum and extracurricular activities and the involvement of parents. Pendidikan memiliki peran penting dalam pembinaan moral Islam (akhlak). Dalam Islam, ajaran akhlak Islam memiliki peranan penting dalam membimbing individu untuk menjalani kehidupan yang saleh. Akhlak dalam Islam pada hakikatnya merupakan nilai dasar dan fondasi karakter seseorang. Penelitian ini berupaya untuk mendeskripsikan dan menganalisis pendidikan akhlak Islam. Penelitian ini menggunakan metode kepustakaan yang menggunakan sumber teks seperti jurnal dan buku. Hasil penelitian ini menunjukkan bahwa pembinaan akhlak Islam menghadapi pengaruh dan tantangan dari paham sekuler global serta kurangnya sumber daya. Adapun solusi dalam menghadapi tantangan ini yang terutama adalah dengan program pelatihan bagi Pendidik. Selanjutnya pendidikan akhlak Islam dapat diimplementasikan dalam kurikulum sekolah melalui integrasi kurikulum dan kegiatan ekstrakurikuler serta keterlibatan Orang Tua. Key Words: Islamic Moral Education, the integration of moral into curriculum, Teacher and Parents role